Rigid two-axis MEMS force plate for measuring cellular traction force. (23rd August 2016) - Takahashi, Hidetoshi; Jung, Uijin G; Kan, Tetsuo; Tsukagoshi, Takuya; Matsumoto, Kiyoshi; Shimoyama, Isao
Abstract: Cellular traction force is one of the important factors for understanding cell behaviors, such as spreading, migration and differentiation. Cells are known to change their behavior according to the mechanical stiffness of the environment. However, the measurement of cell traction forces on a rigid environment has remained difficult. This paper reports a micro-electromechanical systems (MEMS) force plate that provides a cellular traction force measurement on a rigid substrate. Both the high force sensitivity and high stiffness of the substrate were obtained using piezoresistive sensing elements. The proposed force plate consists of a 70 µ m  ×  15 µ m  ×  5 µ m base as the substrate for cultivating a bovine aortic smooth muscle cell, and the supporting beams with piezoresistors on the sidewall and the surface were used to measure the forces in both the horizontal and vertical directions. The spring constant and force resolution of the fabricated force plate in the horizontal direction were 0.2 N m −1 and less than 0.05 µ N, respectively. The cell traction force was measured, and the traction force increased by approximately 1 µ N over 30 min. These results demonstrate that the proposed force plate is applicable as an effective traction force measurement.